Representasi Nilai Pendidikan Islam dalam Tradisi Rabab Pasisia: Analisis Semiotik Kisah Lamang Tanjuang Ampalu - Iswandi Iswandi; Lutfiyani; Yulda Dina Septiana; Mita Fitria (MAN 4 Kota Pekanbaru, 2026)
This study aims to analyze the representation of Islamic educational values in the Rabab Pasisia performance presented by Hasan Basri in the story of Lamang Tanjuang Ampalu. This research employed a qualitative approach with a semiotic analysis method to reveal the meanings embedded in the narrative, symbols, expressions, and musical elements of the performance. The main data source was a performance video analyzed through observation and documentation. The findings indicate that Rabab Pasisia contains a system of signs at three levels of meaning: denotative, connotative, and myth. Denotatively, the story depicts the life of a character facing social conflicts. Connotatively, the performance represents Islamic educational values, such as ṣabr, amanah, and tawakkal, conveyed through narrative and musical expression. At the level of myth, the story reflects the collective values of Minangkabau society integrated with Islamic teachings. This study concludes that Rabab Pasisia functions as a medium of Islamic education based on local wisdom that is effective in shaping community character.